Essential roles of SERKs in the ROOT MERISTEM GROWTH FACTOR-mediated signaling pathway. Issue 1 (3rd February 2022) - Ou, Yang; Tao, Bingqing; Wu, Yujun; Cai, Zeping; Li, Huiqiang; Li, Meizhen; He, Kai; Gou, Xiaoping; Li, Jia
Abstract: ROOT MERISTEM GROWTH FACTORs (RGFs), a group of peptide hormones, play key roles in root apical meristem development. In Arabidopsis ( Arabidopsis thaliana ), there are 11 members of RGFs, in which at least RGF1, RGF2, and RGF3 are expressed at the root tip and are involved in root stem cell niche maintenance. RGFs are perceived by five functionally redundant receptor-like protein kinases, RGF1 INSENSITIVE 1 (RGI1) to RGI5, to maintain the expression of two downstream APETALA 2 (AP2) transcription factor genes, PLETHORA 1 ( PLT1 ) and PLT2, and to stabilize PLT2. RGI1 to RGI3 were also named RGF RECEPTOR 1 (RGFR1) to RGFR3, respectively. Although previous studies have suggested that BRI1-ASSOCIATED RECEPTOR KINASE 1 (BAK1) and its paralogs, SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASEs (SERKs), may act as coreceptors of RGIs, comprehensive genetic and biochemical analyses have not been well documented. Here, we report that single, double, and triple mutants of SERK s show various degrees of short root phenotypes and insensitivity to exogenously applied RGF1. The interaction between RGIs and BAK1 and their mutual phosphorylation are RGF1 dependent. We also found that RGF1-induced MAPK activation relies on both RGIs and SERKs. We demonstrate that RGIs play redundant roles in regulating root apical meristem development. Therefore, we genetically and biochemically substantiated that SERKs, as coreceptors, play essential roles in the RGF1-mediated signaling pathway. Abstract : SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASEs act as the coreceptors of RGF1 INSENSITIVES and play essential roles in the ROOT MERISTEM GROWTH FACTOR-mediated signaling pathway.